Zinc isotopes as tracers of anthropogenic sources and biogeochemical processes in contaminated mangroves. (August 2018) - Araújo, Daniel F.; Machado, Wilson; Weiss, Dominik; Mulholland, Daniel S.; Garnier, Jeremie; Souto-Oliveira, Carlos E.; Babinski, Marly
Abstract: Recent work has shown that variations in zinc (Zn) isotope ratios enable us to identify contamination sources in the terrestrial environment and uptake processes in higher plants. Here in this study, we demonstrate that this also holds true for mangrove forests, which play an important role in the biogeochemical cycling of metals in tropical coastal ecosystems and that are seriously threatened by anthropogenic pollution. To this end, we determined zinc concentration and isotope composition (expressed using the δ 66 Zn notation relative to the JMC 3-0749-L standard) in sediments and tree leaves collected from a mangrove close to Rio de Janeiro in Brazil. The δ 66 ZnJMC values of sediments vary between +0.36 and + 0.84‰ and fall on a mixing line between detrital terrestrial sources (characterized with δ 66 ZnJMC = +0.28 ± 0.12‰, 2σ) and metallurgical ore sources (δ 66 ZnJMC = +0.86‰ ±0.15‰, 2σ). Leaves of Laguncularia racemose, in contrast, showed δ 66 ZnJMC values ranging between +0.08 and + 0.23‰, suggesting that processes including uptake, translocation and bioavailability in the rhizosphere control the isotope composition of zinc in the mangrove plant. Graphical abstract: Highlights: The δ 66 ZnJMC values of mangrove sediments suggest a mixing source processes. Leaves of Laguncularia racemose showed δ 66 ZnJMC values ranging between +0.08 and + 0.23‰. Zn uptake, translocation and bioavailability control the isotope composition of leaves. Zn isotope compositions of leaves may indicate environmental changes in mangrove systems.